Artigos acadêmicos em língua inglesa: uma abordagem multidimensional - Ramos Filho, Etelvo (2014)
This dissertation describes how a corpus of 900 research articles written in English by researchers of 10 fields of study and nine different origins is mapped onto the dimensions of variation proposed by Biber (1988). Its theoretical and methodological underpinnings are provided by Corpus Linguistics and Multidimensional Analysis. The former is an area in Applied Linguistics in which language is seen as a probabilistic system and for whose studies computational tools and corpora are used. The latter is a corpus based approach for the study of dimensions of variations, which uses statistical procedures to identify relationships between linguistic features and registers in large amounts of texts. The methodology included the compilation of a corpus (Corpus of English Research Articles CERA), which is composed of articles collected using the Internet, its processing and analyses based both on origin and field. The result of the analyses for both the origin and the field shows that the corpus is composed of articles whose features characterize them in the 5 dimensions of variation proposed by Biber (1988) as: 1) being informational, 2) being non-narrative, 3) having explicit reference, 4) having non-explicit persuasion, and 5) having abstract information